2022
DOI: 10.1021/acscatal.2c04800
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Methane Dry Reforming over Ni Catalysts via Modulating Surface Electronic Structures of BN Supports by Doping Carbon

Abstract: Methane dry reforming (MDR) attracts great attention due to the comprehensive conversion and utilization of CO2 and CH4 into an equimolar ratio of H2/CO. Boron nitride-supported Ni-based catalysts show great promise for the efficient coking resistance but exhibit weak interactions with active sites and poor gas adsorption capacity. Herein, carbon-doped boron nitride (BCN) was originally developed to anchor Ni nanoparticles on the boundary or near the boundary between layers with strong interactions, which exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Besides, the surface oxygen species derived from the activation of CO 2 would react with carbon from the decomposition of methane, further forming CO, which could enhance the stability of the catalyst . Apart from the oxygen species derived from the decomposition of CO 2 , other oxidation-reducing reactions occurring on catalysts can also provide active adsorbed oxygen species (O*). , Deng et al reported that the O* species derived from the reducible oxides would contribute to the gasification of carbon deposition to form CO or CO 2 . Zhang et al also found that the restraining Ni oxidation and the dynamic variation between MoO x and MoO x C y contributed to the activity and coking resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the surface oxygen species derived from the activation of CO 2 would react with carbon from the decomposition of methane, further forming CO, which could enhance the stability of the catalyst . Apart from the oxygen species derived from the decomposition of CO 2 , other oxidation-reducing reactions occurring on catalysts can also provide active adsorbed oxygen species (O*). , Deng et al reported that the O* species derived from the reducible oxides would contribute to the gasification of carbon deposition to form CO or CO 2 . Zhang et al also found that the restraining Ni oxidation and the dynamic variation between MoO x and MoO x C y contributed to the activity and coking resistance.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Generally, carbon deposition originates from CH 4 decomposition and CO disproportionation. 18,19 Worse will, the sintering of Ni NPs would result in more serious carbon deposition due to well graphitic carbon formation on the large Ni particles. [20][21][22] In order to solve the issues of sintering and carbon deposition, researchers proposed many solutions to improve the activity and stability of the catalysts, such as alloying with other metals, [23][24][25][26] enhancing the strong metal-support interaction (SMSI), [27][28][29] or optimizing supports to expose more active sites.…”
Section: Introductionmentioning
confidence: 99%
“…Noble metals such as Pt, Rh, Ru, Ir, and others have shown excellent catalytic activity for DRM. 11,21,[30][31][32][33][34] Over the years, efforts have been made to replace the expensive and rare noble metal-based catalysts with naturally abundant non-noble metals like Ni, Co, Cu, Zn, etc., based catalysts, [35][36][37] which have shown promising results towards catalyzing the DRM reaction. Ni especially has exhibited great potential for catalyzing the process, but its activity signicantly reduces due to coke deposition at high temperature.…”
Section: Introductionmentioning
confidence: 99%